PEMBERDAYAAN KADER DALAM UPAYA PENINGKATAN PENGETAHUAN DAN SOSIALISASI PENCEGAHAN DINI MALARIA DI WILAYAH KERJA PKM SRI KUNCORO KECAMATAN PONDOK KELAPA KABUPATEN BENGKULU TENGAH TAHUN 2024 - Tedy Febriyanto; Jon Farizal; Putri Widelia W; Evi Fitriyani; Yunita, Yunita (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2025)
Malaria is an infectious disease that is still a public health problem in Indonesia. Malaria is caused by protozoa of the Plasmodium group, which is transmitted through mosquito bites. Anopheles sp mosquitoes carry the spinfective Plasmodium parasite which enters the human body through the bite of female mosquitoes. The Plasmodium sp parasites found in humans consist of Plasmodium malariae, Plasmodium vivax, Plasmodium falciparum, Plasmodium ovale and the most recently discovered plasmodium is Plasmodium Knowles. This community service aims to move people to live healthy lives and actively prevent malaria through efforts to increase knowledge and socialize malaria prevention in the PKM Sri Kuncoro Working Area, Central Bengkulu Regency. Method: There are three steps in this community service, namely preparation, implementation, evaluation and monitoring. It is hoped that this activity can increase public knowledge about malaria prevention and move people to live healthy lives. Results: This community service provides insight and knowledge to the community in recognizing clinical symptoms of malaria and forming groups. Conclusion: A team has been formed that has been given knowledge about malaria, information on malaria prevention and information about laboratory examinations that support malaria examinations consisting of cadres in each village and posyandu to carry out information on malaria prevention and health awareness community movements in the Sri Kuncoro Community Health Center Working Area Pondok Kelapa District, Central Bengkulu Regency